An application case of ecological indicator values (Zeigerwerte) calculated with a simple algorithmic approach - Fanelli, G.; Pignatti, S.; Testi, A. (Plant Biosystems - An International Journal Dealing with all Aspects of Plant Biology, 2007)
Abstract The vegetation of the study site near Rome (Castelporziano Estate), where different woodland types occur, was analysed on the basis of ecological indicator values (Zeigerwerte) for light, temperature, continentality of climate, soil moisture, soil pH and nitrogen. Indicator values were estimated with Hill's reprediction algorithm for the flora of Central-Southern Italy relying on a database of 4,207 original relevés representing a balanced survey of the vegetation of this and surrounding areas. It was possible to obtain indicator values for an important fraction of the Italian Mediterranean flora. Results are ecologically reasonable, and it was possible to find strong correlation between the recalculated values and a few environmental variables. These correlations were not significant in an analogous test with subjectively derived scores of Ellenberg indicator values.
From Duplicate 1 (An application case of ecological indicator values (Zeigerwerte) calculated with a simple algorithmic approach - Fanelli, G; Pignatti, S; Testi, A)
Keywords: correlation; Italy; reprediction algorithm; vegetation ecology